Customer relation and customer attitude the case of Makinaugalingon printer and bookbinder company - Farillon, Cherrylane; Nillos, Ernesto; Yap, Carlo (2005)
This study aims to know the effects of customer relations to customer attitude in a printing and bookbinding company. Descriptive research was used to seek answers to some problems in the study. The researchers chose 20 respondents at random by means of lottery. after the data were gathered and evaluated it revealed that customer relations has an effect on customer attitude in dealing with the company. After the analysis of data the researchers concluded that the company has good communication with its customer and the company has good ways to maintain and obtain their customer. Researcher also recommended the following : 1. The company should monitor he feedbacks from the customers ; 2. Improvement of the behavior of some employees ; 3. Handle complaints and feedback effectively and taking necessary actions on those issues ; 4. Continue its good and reasonable services to its customers.
Research Paper (Mgt 199-Management Research). -- [Iloilo City : UPV-CM], October 20, 2005.